2009
DOI: 10.1128/mcb.00898-08
|View full text |Cite|
|
Sign up to set email alerts
|

p27Kip1 Inhibits Cyclin D-Cyclin-Dependent Kinase 4 by Two Independent Modes

Abstract: Cell cycle progression is regulated by cyclin-dependent kinases (cdk's), which in turn are regulated by their interactions with stoichiometric inhibitors, such as p27 Kip1 . Although p27 associates with cyclin D-cyclindependent kinase 4 (cdk4) constitutively, whether or not it inhibits this complex is dependent on the absence or presence of a specific tyrosine phosphorylation that converts p27 from a bound inhibitor to a bound noninhibitor under different growth conditions. This phosphorylation occurs within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
116
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(125 citation statements)
references
References 41 publications
5
116
1
2
Order By: Relevance
“…8,16,20 On the other hand, as first exemplified by T187 phosphorylation of p27, 21 phosphorylations of Cip/Kip proteins, including by oncogenic tyrosine kinases, have also emerged as other potential mechanisms for CDK regulation. [22][23][24] Consistent with this idea, we have recently demonstrated that S130 phosphorylation of p21 inside the cyclin D-CDK4/6 complexes is catalyzed by other active CDK4/6 and CDK2 complexes and is required for the activating T172 phosphorylation of p21-bound CDK4 complexes. 15 Later at G1/S transition, S130 phosphorylation of p21 leads to its recognition by the SCF/Skp2 ubiquitin ligase complex and proteasomal degradation of cyclin/CDK-bound p21, hence contributing to CDK2 activation.…”
Section: Introductionsupporting
confidence: 58%
“…8,16,20 On the other hand, as first exemplified by T187 phosphorylation of p27, 21 phosphorylations of Cip/Kip proteins, including by oncogenic tyrosine kinases, have also emerged as other potential mechanisms for CDK regulation. [22][23][24] Consistent with this idea, we have recently demonstrated that S130 phosphorylation of p21 inside the cyclin D-CDK4/6 complexes is catalyzed by other active CDK4/6 and CDK2 complexes and is required for the activating T172 phosphorylation of p21-bound CDK4 complexes. 15 Later at G1/S transition, S130 phosphorylation of p21 leads to its recognition by the SCF/Skp2 ubiquitin ligase complex and proteasomal degradation of cyclin/CDK-bound p21, hence contributing to CDK2 activation.…”
Section: Introductionsupporting
confidence: 58%
“…63 As a consequence, ATP is able to bind to the catalytic cleft of the kinase and restores partial kinase activity to the p27-bound cyclin/Cdk complex. 6,15,18,53,63,64 Tyrosine 88 phosphorylation partially restored phosphorylation of histone H1 by p27-Cdk2/cyclin A and pRb by p27-cyclin A/Cdk2 or p27-cyclin D1/Cdk4. 63 Thus, Y88 phosphorylation impairs the ability of p27 to inactivate Cdks.…”
Section: Oncogenic Jak2v617f Phosphorylates and Inactivates P27mentioning
confidence: 99%
“…13 In addition, binding of p27 can prevent the activating phosphorylation of the Cdk subunit by Cdk-activating kinase (CAK). 14,15 While inactivation of cyclin A/Cdk2 by p27 has been resolved at the molecular level, the mechanisms of p27 regulating the activity of cyclin D/Cdk4 or cyclin D/ Cdk6 complexes has long remained an issue of debate, as both, kinase-active and kinase-inactive complexes with p27 exist. 6,16,17 A recent thermodynamic analysis of the interactions of p27 with cyclin D1/Cdk4 and cyclin A/Cdk2 suggests that, even though the K d values and IC 50 of p27 for both Cdk complexes are essentially identical, different thermodynamic forces govern p27 subdomain binding.…”
Section: The Structural Basis For Cdk Inhibition By P27mentioning
confidence: 99%
See 1 more Smart Citation
“…Arguing for a two state mechanism, Dr. Blain's group has assiduously sought-after, and shown that p27 KIP1 can be both a CDK4 bound inhibitor, and a bound non-inhibitor, depending on the growth state of the cell (Ray et al, 2009). They also have discovered that p27 KIP1 associates with cyclin D/CDK4 constitutively, and that a specific tyrosine phosphorylation converts p27 KIP1 from a bound inhibitor to a bound non-inhibitor under different growth conditions.…”
Section: Interaction Of P27 Kip1 With Cyclin/cdk Complexes and Its Inmentioning
confidence: 99%